2017
DOI: 10.1016/j.envres.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of individual and area-level factors as modifiers of the association between warm-season temperature and pediatric asthma morbidity in Atlanta, GA

Abstract: Introduction Previous studies have found associations between respiratory morbidity and high temperatures; however, few studies have explored associations in potentially sensitive sub-populations. Methods We evaluated individual and area-level factors as modifiers of the association between warm-season (May–Sept.) temperature and pediatric respiratory morbidity in Atlanta. Emergency department (ED) visit data were obtained for children, 5–18 years old, with primary diagnoses of asthma or respiratory disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 75 publications
(112 reference statements)
4
32
0
4
Order By: Relevance
“…Computerized billing records on ED visits were acquired from the Georgia Hospital Association for all 38 nonfederal acute care hospitals with emergency departments in the 20-county Atlanta metropolitan area for the study period ( O’Lenick et al 2017 ; Sarnat et al 2010 ). Patient variables included date of admission, all recorded International Classification of Diseases, Ninth Revision (ICD-9) diagnostic codes, date of birth, sex, race, and five-digit residential ZIP code.…”
Section: Methodsmentioning
confidence: 99%
“…Computerized billing records on ED visits were acquired from the Georgia Hospital Association for all 38 nonfederal acute care hospitals with emergency departments in the 20-county Atlanta metropolitan area for the study period ( O’Lenick et al 2017 ; Sarnat et al 2010 ). Patient variables included date of admission, all recorded International Classification of Diseases, Ninth Revision (ICD-9) diagnostic codes, date of birth, sex, race, and five-digit residential ZIP code.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, a study reported lagged effects for temperature-related and paediatric asthma emergency visits, suggesting that children are at risk for increased asthma morbidity when temperatures are high, on average, for several days. In detail, estimated Relative Risks (RRs) for maximum temperatures and asthma emergency visits were positive and significant for lag days 1-5, with the strongest single-day association observed on lag day 2 (RR = 1.06, 95% CI: 1.03, 1.09) for a change in the T max from 27 • C to 32 • C (25th to 75th percentile) [28].…”
Section: Temperaturementioning
confidence: 97%
“…Além disso, o efeito do frio e do calor se manifestam em tempos diferentes no organismo, as temperaturas mais baixas tendem a ter um efeito mais prolongado e as temperaturas altas apresentam um efeito curto e imediato 7,19 .…”
Section: Discussionunclassified
“…Percebe-se que os resultados deste estudo divergem das diversas contribuições científicas 6,7,8,11,19,35 que apontam que os efeitos da exposição ao frio, ao calor e à ocorrência de temperaturas extremas são significativos, para o aumento do risco de morte por doenças respiratórias. Cabe notar, também, essa diferença de resultados pela identificação dos padrões das curvas do risco e nos gráficos, pois as curvas da relação entre temperatura média do ar e as internações não seguem as formas de curvas do padrão U, J e V encontradas na literatura atual, especialmente nos estudos que relacionam a temperatura com a mortalidade.…”
Section: Discussionunclassified